Effect of the herbicide clifosit on population Azotobacter chroococcum and Rhizobium leguminosarum (Journal of the College of Basic Education, 2023)
The results showed the effect of the weed killer clifosit at the recommended dose and weaklyThe recommended dose in the population of Bacterium 077002020007077./ and that the effect dependedon the type of bacteria, the concentration of the pesticide, and the time period after treatment. No exterminator occurredClayphosate at the recommended dose had a significant effect on the bacterial population after 3 and 60 daysdays of treatment as it reached 105 x 80 CFU / 1 gm soil 83 x 01colony-forming unit/1g of soil, while causing a significant reduction in the population of bacteriatwice the recommended dose after 3 days and 60 days of treatment, as it reached 61 x 01CFU / 1g and 56 x 105 CFU / 1g soilTwo comparisons to the control treatment, which recorded 105 x 81 CFU/1g.soil and 85 CFU / 1 gm soil, respectively. The results showed thatCliphosate showed a significant effect on the population of bacteria. e0sun bad! m after3 days and 60 days of treatment as it recorded 01" x 13 CFU / 1gSoil 81 CFU / 1 gm soil, while the double dose was induced